Roots and stems of Kadsura coccinea extract induced developmental toxicity in zebrafish embryos/larvae through apoptosis and oxidative stress. (1st January 2020) - Xia, Zhongshang; Hao, Erwei; Chen, Zhangmei; Zhang, Mingzhe; Wei, Yanting; Wei, Man; Hou, Xiaotao; Du, Zhengcai; Deng, Jiagang
Abstract: Context: Although the roots and stems of Kadsura coccinea (Lem.) A. C. Smith. [Schisandraceae] are herbs and traditional foods in Li nationality, its toxicity remains unclear. Objective: To study developmental toxicity of K. coccinea consumption and explain underlying mechanisms. Materials and methods: Zebrafish were applied to assess LC50 values of hydroethanol extract (KCH) and water extract (KCW) of Kadsura coccinea . In further study, three concentrations groups of KCH (3.75, 7.5 and 15 μg/mL for embryo, 7.5, 15 and 30 μg/mL for larvae) and control group ( n  = 30) were administered. At specific stages of zebrafish development, spontaneous movement, hatching rate, etc., were measured. Gene expressions related to developmental toxicity were examined. Results: The LC50 value of KCH (24 or 45 μg/mL) was lower than KCW (1447 or 2011 μg/mL) in embryos or larvae. The inhibited spontaneous movement (20%), hatching rate (20%), body length (12%) and eye area (30%) were observed after KCH treatment. Moreover, the decreased liver areas (25%) and fluorescence intensity (33%), increased ALT (37%) and AST levels (42%) were found in larvae treated with KCH (30 μg/mL). The increased ROS (89%), MDA concentrations (30%), apoptosis generation (62%) and decreased T-SOD activity (16%) were also observed. The represented genes of developmental hepatotoxicity, oxidative stress and apoptosis in zebrafish were activated after KCH (15 or 30 μg/mL) treatment. Discussion and conclusions: These results demonstrate that KCH has developmental toxicity on zebrafish. Our study provides a scientific basis for further research on the toxicity of Kadsura coccinea .